Eurasian Call for the Project «Integration of Integrations» - Nikolai Maratovich Mezhevich (Управленческое консультирование)
In today’s rapidly changing world integration is one of the possibilities of sustainable development of countries, and in view of the growing role of large state associations, increasing the likelihood of integration project. For various reasons the implementation of this project currently is not possible. Whether the authorities of both the European Union and Russia could overcome the crisis of relationships, it can bring positive results. The purpose of this article is to highlight the main negative aspects affecting the development of integration processes and to analyse existing approaches to the development of integration unions. A distinctive feature of the existing problems should be considered as practical rather than theoretical complexity.